Impact damage in woven carbon fibre/epoxy laminates: analysis of damage and dynamic strain fields. (2017) - Coles, Laurence A.; Roy, Anish; Voronov, Leonid; Semenov, Sergey; Nikhamkin, Mikhail; Sazhenkov, Nickolay; Silberschmidt, Vadim V.
Abstract: In this study the resultant ballistic dynamic response observed in a 2x2 twill weave T300 carbon fibre/epoxy composite flat-plate specimen is examined, using a combination of non-invasive analysis techniques. The study investigates deformation and damage caused by impacts of two types of projectiles: solid (steel) travelling with velocity of 70-90 m/s, and fragmenting (ice) with the velocity in the range of 300-500 m/s. Digital image correlation was employed to obtain displacement and to estimate dynamic strain fields from the rear surfaces of the specimens during each experiment. 3D X-ray computer tomography (CT) was used to image and visualize the resultant damage inside the samples. It was shown that solid projectiles lead to greater localized deformation and in some cases penetration, whereas fragmenting projects destroyed on impact cause a more distributed impact load but can lead to major front-surface damage depending on the depth of indentation before fragmentation.